High PUFA Oral Nutritional Supplementation’s Effect on Advanced Cervical Cancer Patients’ Nutritional Status - wuryanti, sri (Universitas Muhammadiyah Yogyakarta, 2024)
While weight loss occurs in patients with cancer, PUFA may suppress cancer growth. This study aims to determine the high PUFA nutritional supplementation’s effect on the nutritional status of patients with advanced cervical cancer who received radiotherapy. This study was a double-blind Randomized Clinical Trial on patients with advanced cervical cancer. Subjects were taken consecutively, through randomization, divided into treatment and control groups. Thirty-one patients were involved as respondents, with 16 in the treatment groups and 15 in the control groups. The findings revealed that socio-demographic status, omega-6 and omega-3 fatty acid intake patterns, and nutritional and clinical status were not significantly different between groups before treatment. Nutritional supplementation was provided as ONS labeled A and B, taken three times a day. During treatment, patients were asked to record all food and beverages consumed in the intake book at least three days a week, including two working days and one day off. The treatment group’s body weight was relatively more stable, while the control group tended to decrease in weight, but the ∆ weight loss in each group was not significantly different (p = 0.149). PUFA supplementation can maintain the nutritional status of patients with cervical cancer by maintaining body weight.